Malay borrowings in the Punjabi language - Kaur, Baljit (Journal of Modern Languages, 2017)
The purpose of this study is to identify the Malay lexical borrowings in the Punjabi spoken language in Malaysia using the synchronic approach, and to classify these borrowings using the criteria put forward by Haugen and Stene. The scope of the study will be limited to family dialogue and will attempt to cover some common social themes to capture the usage of Malay words and terms in daily occurrences. It is not the intention of the writer to prove or disprove any theory or research findings in studies which have been carried out on the Punjabi language before. No previous research is available on which to develop a theory or research hypothesis. However, research of a similar nature exists with regard to other languages. This study is therefore in a way an extension of the research conducted on other languages.